2020
DOI: 10.15694/mep.2019.000159.2
|View full text |Cite
|
Sign up to set email alerts
|

Students Advocating for Diversity in Medical Education

Abstract: Thank you to our reviewers who provided feedback on our manuscript. As per the reviewer suggestions we have included expanded examples and descriptions to provide a richer picture of the program. Additional information is also included about the program sustainability through faculty, staff, administration, and student support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Our findings resemble that of Muntinga et al (2016) who point to a lack of diversity in the content of the medical curriculum in the areas of patient-physician communication (e.g., communicating with diverse patients in terms of gender, class, and culture), developing medical knowledge and skills (e.g., diagnosing diverse patients, disease prevalence in diverse patients), and reflection on students’ and health care professionals’ own awareness, biases, and assumptions [ 36 ]. Our study also aligns with research that showed students perceive gaps in the medical curriculum related to diversity issues [ 11 13 ]. The notion of social responsibility points to the importance of medical educators preparing students to serve a diverse society to help eliminating disparities and create socially responsible health care professionals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings resemble that of Muntinga et al (2016) who point to a lack of diversity in the content of the medical curriculum in the areas of patient-physician communication (e.g., communicating with diverse patients in terms of gender, class, and culture), developing medical knowledge and skills (e.g., diagnosing diverse patients, disease prevalence in diverse patients), and reflection on students’ and health care professionals’ own awareness, biases, and assumptions [ 36 ]. Our study also aligns with research that showed students perceive gaps in the medical curriculum related to diversity issues [ 11 13 ]. The notion of social responsibility points to the importance of medical educators preparing students to serve a diverse society to help eliminating disparities and create socially responsible health care professionals.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to the findings from a survey among a large sample of medical students about their preparedness and skillfulness in providing care to patients from diverse cultures that showed most medical students did not feel adequately prepared to provide care to diverse patients by their final year of education [ 12 ]. Also, students from a U.S. medical school pointed to gaps they observed in the curriculum and advocated for the establishment of a comprehensive curriculum that would adequately prepare them to work with diverse populations [ 13 ]. In short, in the traditional medical culture, diversity does not seem a central aspect of health care.…”
mentioning
confidence: 99%
“…Aligned with industry recommendations and initiatives to transform clinical learning environments, 1–4 a collaborative and systematic approach was developed to audit preclerkship courses, document gaps, and identify opportunities for enhancement.…”
Section: Approachmentioning
confidence: 99%
“…The cultural diversity of students themselves is a strength that brings diversity of perspectives and experience relevant to working with patients, communities and healthcare teams. Primary care should adopt inclusive, evidence-based learning strategies that take account of the needs, preferences, circumstances and strengths of diverse students [31]. Examples may include small group reflective discussions and project work that value and are enriched by diverse student perspectives, thereby benefitting all students.…”
Section: Curriculum Contentmentioning
confidence: 99%